Hubungan Kadar Hemoglobin terhadap Saturasi Oksigen pada Pasien Rawat Inap Penyakit Paru Obstruktif Kronis (PPOK) Eksaserbasi Akut di RSUD dr. Suhatman Mars Kota Dumai - Octariany; Surya Arfa (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive chronic respiratory disease that has become a global health concern due to its high morbidity and mortality rates and its impact on patients’ quality of life. In acute exacerbation conditions, impaired oxygenation becomes a major problem that may be influenced by various factors, including hemoglobin levels as the primary component of oxygen transport in the blood. However, the relationship between hemoglobin levels and oxygen saturation in patients with acute exacerbation COPD remains inconsistent, particularly in populations exposed to high environmental risk factors. This study aimed to determine the relationship between hemoglobin levels and oxygen saturation in patients with acute exacerbation COPD hospitalized at RSUD dr. Suhatman MARS Dumai, Kota Dumai. This research employed an analytic observational design with a cross-sectional approach involving 73 patients selected through total sampling based on medical record data. Bivariate analysis using the Spearman correlation test showed no significant relationship between hemoglobin levels and oxygen saturation (r = 0.098; p = 0.412), indicating a very weak and statistically insignificant correlation. The study concluded that hemoglobin levels do not directly influence the oxygenation status of patients with acute exacerbation COPD, where impaired oxygenation is more strongly affected by respiratory factors such as ventilation-perfusion imbalance and structural lung damage. The novelty of this study lies in its empirical evidence demonstrating the limited role of hemoglobin as a predictor of oxygenation in patients with acute exacerbation COPD within a population with specific environmental characteristics, thereby providing a basis for developing more comprehensive clinical approaches in monitoring and managing COPD patients.